Some properties of operator-valued frames. Issue 2 (March 2016) - GĂVRUŢA, Laura; GĂVRUŢA, Paşc
Abstract: Operator-valued frames (or g -frames) are generalizations of frames and fusion frames and have been used in packets encoding, quantum computing, theory of coherent states and more. In this article, we give a new formula for operator-valued frames for finite dimensional Hilbert spaces. As an application, we derive in a simple manner a recent result of A. Najati concerning the approximation of g -frames by Parseval ones. We obtain also some results concerning the best approximation of operator-valued frames by its alternate duals, with optimal estimates.